2013
DOI: 10.1002/jgrd.50357
|View full text |Cite
|
Sign up to set email alerts
|

Roughness metrics of prismatic facets of ice

Abstract: [1] We define a surface normal roughness metric for mesoscopically rough ice facets and present methods for inferring its value from variable pressure scanning electron micrographs. The methods rely on the anisotropic morphology of roughening in the prismatic plane, in which nearly all the variation in surface height occurs in the direction of the main symmetry axis of hexagonal-habit ice prisms. Because of this symmetry, roughening appears at boundaries between prismatic facets in a way that readily permits q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 53 publications
11
49
0
Order By: Relevance
“…This finding was based on cloud chamber measurements of the angular scattered intensity from a collection of ice crystals at a visible wavelength, and comparisons between measurements and ray-tracing results showed that the Weibull statistics were the better match to the measurements. Moreover, the choice of Weibull statistics is consistent with independent cloud chamber results found by Neshyba et al (2013). For the most randomised case considered in this paper, the Weibull statistics are assumed to have the following scale and shape parameter values of 0.4 and 0.85, respectively, and for the spherical air bubble inclusions, a mean free path of 200 µm is assumed (Baran and Labonnote, 2007).…”
Section: The Single-scattering Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding was based on cloud chamber measurements of the angular scattered intensity from a collection of ice crystals at a visible wavelength, and comparisons between measurements and ray-tracing results showed that the Weibull statistics were the better match to the measurements. Moreover, the choice of Weibull statistics is consistent with independent cloud chamber results found by Neshyba et al (2013). For the most randomised case considered in this paper, the Weibull statistics are assumed to have the following scale and shape parameter values of 0.4 and 0.85, respectively, and for the spherical air bubble inclusions, a mean free path of 200 µm is assumed (Baran and Labonnote, 2007).…”
Section: The Single-scattering Propertiesmentioning
confidence: 66%
“…The former method removes the 46 • halo and reduces the 22 • halo (Macke et al, 1996b;Yang et al, 2008), and the latter method produces featureless phase functions through multiple scattering between spherical air inclusions Baran and Labonnote, 2007;Xie et al, 2009). Although recent cloud chamber and theoretical ray-tracing studies by Neshyba et al (2013) and Shcherbakov (2013), respectively, have shown that surface roughness may not necessarily completely remove the 22 • halo, it is as yet unclear as to whether the results obtained in the laboratory are scalable to the real atmosphere. Indeed, in situ studies on the occurrence of the 22 • halo show that it is a rare event (Field et al, 2003;Gayet et al, 2011;Ulanowski et al, 2013).…”
mentioning
confidence: 99%
“…This distortion parameterization can be considered as a proxy for the randomization of the angles between parts of crystal facets caused by crystal surface roughening or other distortions of the solid hexagonal structure of ice crystals (Yang et al 2008;Liu et al 2014a). Comparisons between various definitions and parameterizations of crystal surface roughness are provided by Neshyba et al (2013) and Geogdzhayev and van Diedenhoven (2015). The increase of asymmetry parameter with aspect ratio deviating from unity is somewhat stronger for plates than for columns when plotted on a logarithmic scale as in Fig.…”
Section: The Definition Of Ensemble-average Aspect Ratio and Distortimentioning
confidence: 99%
“…Furthermore, recent electron-microscopic imaging studies on ice crystals (Neshyba et al 2013;Magee et al 2014) show potential to provide physical ice surface roughness metrics and to determine how crystal roughness varies with temperature and humidity. Such measurements help constrain optical models for climate models or radiative closure studies such as conducted by Kindel et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it is an approximation of the effects of roughened surface texture (Neshyba et al, 2013) and other kinds of imperfections present in natural ice cloud particles. The scattering properties calculated by this approximate method are in reasonable agreement with those calculated by rigorous ray-tracing methods (Yang et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%